A TODIM-based approach for environmental impact assessment of pumped hydro energy storage plant. (1st March 2020) - Lu, Zhiming; Gao, Yan; Zhao, Wenhui
Abstract: Making environmental impact assessment (EIA) is extremely vital to the green development of pumped hydro energy storage plants (PHESPs). But, three critical issues have not been addressed. First, some key environmental factors having big influences on PHESP have not been identified and evaluated. Second, massive of information loss and distortion exist in current research. Third, there is a lack of a systematic and clear framework for EIA of PHESP. To handle the above three problems and make EIA of PHESP more reasonable, innovations are made from the following aspects: first, to fully reflect environmental characteristics of PHESP, a comprehensive and rational EIA evaluation criteria system including four criteria is built. Second, a group decision-making model is proposed by combining uncertain linguistic variables (ULVs), triangular fuzzy number (TFN) and TODIM (an acronym in Portuguese of interactive and multiple attribute decision making), this model can effectively reduce information loss and distortion. Third, an integrated decision-making framework is constructed from the perspective of system science, this framework can make EIA easy and efficient. Besides, a case study is employed to validate the practicability and effectiveness of the improvements made above. The results show that the proposed framework is of great use for performing EIA of PHESP, and PHESP A 1 performs best among the four alternatives in the environmental aspect. Meanwhile, sensitivity analysis shows that the ranking of four alternatives is very stable; comparative analysis proves that the proposed model is more effective than fuzzy Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) method in reflecting gaps among four alternatives, because its standard deviation 0.360 is bigger than the standard deviation 0.153 gotten by the fuzzy TOPSIS method. Finally, some valuable managerial implications are put forward to the project managers to guide the practical work. Highlights: An evaluation criteria system is established for EIA of PHESP. The TODIM-based group decision model can reduce information loss and distortion. The integrated framework proposed has good practicability and effectiveness.